High Frequency of Thermodesulfovibrio spp. and Anaerolineaceae in Association with Methanoculleus spp. in a Long-Term Incubation of n-Alkanes-Degrading Methanogenic Enrichment Culture - Liang, Bo; Wang, Li-Ying; Zhou, Zhichao; Mbadinga, Serge M.; Zhou, Lei; Liu, Jin-Feng; Yang, Shi-Zhong; Gu, Ji-Dong; Mu, Bo-Zhong (Frontiers in Microbiology, 2016)
In the present study, the microbial community and functional gene composition of a long-term active alkane-degrading methanogenic culture was established after two successive enrichment culture transfers and incubated for a total period of 1750 days. Molecular analysis was conducted after the second transfer (incubated for 750 days) for both the active alkanes-degrading methanogenic enrichment cultures (T2-AE) and the background control (T2-BC). A net increase of methane as the end product was detected in the headspace of the enrichment cultures amended with long-chain n-alkanes and intermediate metabolites, including octadecanoate, hexadecanoate, isocaprylate, butyrate, isobutyrate, propionate, acetate and formate were measured in the liquid cultures. The composition of microbial community shifted through the successive transfers over time of incubation. Sequences of bacterial and archaeal 16S rRNA gene (16S rDNA) and mcrA functional gene indicated that bacterial sequences affiliated to Thermodesulfovibrio spp. and Anaerolineaceae and archaeal sequences falling within the genus Methanoculleus were the most frequently encountered and thus represented the dominant members performing the anaerobic degradation of long-chain n-alkanes and methanogenesis. In addition, the presence of assA functional genes encoding the alkylsuccinate synthase α subunit indicated that fumarate addition mechanism could be considered as a possible initial activation step of n-alkanes in the present study. The succession pattern of microbial communities indicates that Thermodesulfovibrio spp. could be a generalist participating in the metabolism of intermediates, while Anaerolineaceae plays a key role in the initial activation of long-chain n-alkane biodegradation.